2009
DOI: 10.1002/lary.20498
|View full text |Cite
|
Sign up to set email alerts
|

Rhinovirus enhances various bacterial adhesions to nasal epithelial cells simultaneously

Abstract: These findings suggest that increased expression of host cell adhesion molecules may be the mechanism accounting for the increase in susceptibility to bacterial rhinosinusitis associated with rhinovirus-induced upper respiratory infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
110
0
10

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(127 citation statements)
references
References 21 publications
7
110
0
10
Order By: Relevance
“…Increased attachment of bacteria to virus-infected cells and tissue has been observed for numerous combinations of respiratory pathogens, some of which will be discussed in more detail below (Avadhanula et al, 2006;Golda et al, 2011;Ha kansson et al, 1994;Hament et al, 2004;Jiang et al, 1999;Raza et al, 1993;Sanford & Ramsay, 1987;Wang et al, 2009). Generally, bacterial attachment can be enhanced by (1) increased expression of host receptors after viral infection or (2) by viral structures serving as coupling agents for bacteria to host tissues.…”
Section: Enhancement Of Bacterial Bindingmentioning
confidence: 99%
“…Increased attachment of bacteria to virus-infected cells and tissue has been observed for numerous combinations of respiratory pathogens, some of which will be discussed in more detail below (Avadhanula et al, 2006;Golda et al, 2011;Ha kansson et al, 1994;Hament et al, 2004;Jiang et al, 1999;Raza et al, 1993;Sanford & Ramsay, 1987;Wang et al, 2009). Generally, bacterial attachment can be enhanced by (1) increased expression of host receptors after viral infection or (2) by viral structures serving as coupling agents for bacteria to host tissues.…”
Section: Enhancement Of Bacterial Bindingmentioning
confidence: 99%
“…In primary human nasal epithelial cells, it has been demonstrated that rhinovirus infection up-regulates the expression of cellular fibronectin [54,56]. The up-regulation of fibronectin was observed at both transcriptional and translational levels and seems to be related to the rhinovirus-induced NFκB activation [56].…”
Section: Mechanisms Involved In Interactions Between Staphylococcus Amentioning
confidence: 99%
“…Fibronectin is thus acting as a bridge between S. aureus and the host cell, and the complex formed by FnBPA/B, fibronectin and α5β1 integrin leads to S. aureus internalization inside the epithelial cell [57]. Then the up-regulation of fibronectin expression in epithelial cells during rhinovirus infection could explain the increase of S. aureus epithelial cells adhesion [54,56]. …”
Section: Mechanisms Involved In Interactions Between Staphylococcus Amentioning
confidence: 99%
See 1 more Smart Citation
“…Pseudomonas aeruginosa высевается у пациентов при нозокоми-альном синусите, муковисцидозе, при иммунодефицит-ных состояниях, в том числе ВИЧ-инфекции [4,5]. Кроме того, в последнее время у пациентов c острым бактериаль-1 e-mail: savllena@gmail.com 2 e-mail: zharkih@yandex.ru ным риносинуситом без иммунологических нарушений отмечается рост St. aureus [6]. В целом в РФ ОБРС пневмо-кокковой этиологии встречается в 44,9% во всех возраст-ных группах, в 17,3% его причиной является Haemophilus influenza (данные культурального исследования содержи-мого синуса, полученного путем аспирации) [7].…”
Section: © коллектив авторов 2016unclassified